Production of polyomavirus structural protein VP1 in yeast cells and its interaction with cell structures - Palková, Z; Adamec, T; Liebl, D; Stokrová, J; Forstová, J (FEBS letters, 2000)
The gene for mouse polyomavirus major structural protein VP1 was expressed in Saccharomyces cerevisiae from the inducible GAL7 promoter. VP1 pseudocapsids were purified from cell lysates. Their subpopulation contained fragments of host DNA, which, in contrast to those of VP1 pseudocapsids produced in insect cells, did not assemble with cellular histones into pseudonucleocores. VP1 pseudocapsids accumulated in the yeast cell nuclei. A strong interaction of VP1 with tubulin fibres of the mitotic spindle was observed. The fibres of spindles were larger in diameter, apparently due to tight VP1 binding. Substantial growth inhibition of yeast cells producing VP1 was observed.
Keywords: Fluorescent Antibody Technique, Indirect; Saccharomyces cerevisiae; fluorescenční protilátková technika nepřímá; Spodoptera; Cell Line; buněčné jádro; Microscopy, Electron; Southernův blotting; Protein Binding; kapsida; elektronová mikroskopie; DNA fungální; rekombinantní proteiny; virové plášťové proteiny; buněčné dělení; Blotting, Southern; Cell Division; Mice; Capsid Proteins; Spindle Apparatus; aparát dělícího vřeténka; Capsid; Cell Nucleus; Tubulin; zvířata; DNA, Fungal; vazba proteinů; myši; buněčné linie; tubulin; Recombinant Proteins; Animals